Functional biology of parasitic plants: a review - Těšitel, Jakub (Plant ecology and evolution, 2016)
Background - Parasitic plants are functionally specialized to acquire at least some essential resources from other plants via specialized organs called haustoria. Parasitism evolved 12 times independently in the evolution of angiosperms of which approximately 1% (4500 species) are parasitic. Not only are parasitic plants diverse in terms of evolutionary origins but also in terms of their physiological functioning and ecological behaviour. Methods - Here, I review the importance of principal functional traits which underlie the physiology and ecology of individual parasitic plants. These include the ability to perform photosynthesis, anatomical details of the vascular connection to the host determining the quality of resources acquired from the host, location of the haustoria on the host, which is closely connected with the parasite life form, and the mode of germination (either triggered by environmental condition or induced by presence of host roots). Results and conclusions - Based on the distribution of all these traits in parasitic plants, I introduce their functional classification into root hemiparasites, root holoparasites, stem parasites and endophytic parasites. In addition to the classification, I also present an evolutionary hypothesis explaining the evolution of advanced parasitic plant forms from root hemiparasites. This hypothesis is based on ecological constraints from which the parasites are released with increasing ability to acquire resources from the host. This evolutionary process also implies increasing host specificity which imposes new constraints on the ability to establish host connection. This explains the evolutionary stability of photosynthetic hemiparasites and their species richness which is one order of magnitude higher than that of holoparasites.